Proyecto de implementación de un estudio audiovisual en la ciudad de Babahoyo - Arroyo Castro, Carlos Andrés (2010)
This Project includes a market research, a technical research, an administrative research and a financial research, in order to set up an audiovisual studio in Babahoyo, Ecuador. Today’s trend shows that audiovisual media have taken indisputable prominence in Ecuadorian and worldwide advertising, and have become the most powerful, effective tool in corporative communication. Because of this, there are specialized companies dedicated to cover this demand, and most of them are established in the “big cities”, like Guayaquil or Quito. In Babahoyo specifically, businessmen have the best intentions to use these services, but there is no company that supply these requirements. Because of that, it is suggested creating the studio in this city. The company offers to the customer the best advertisement consultancy and audiovisual services, and its target market is: people that run their own business, and companies that works in different industrial areas with higher production levels. The market research includes data that allows us to determine the feasibility of the project, preferences, will of investment, satisfaction level, and so on. The technical research and the administrative research shows the resources needed to set up the studio: workplace, equipment, staff, etc. The financial research includes a list of the required equipment and investments costs; and also includes an estimation of the production levels for five years since the establishment.